Formulation and In Vitro Evaluation of Acyclovir Mucoadhesive Microspheres for Intravaginal Application: Acyclovir Mucoadhesive Microspheres - Arshad Bashir Khan; Ram Sharnagat Thakur (Iranian Journal of Pharmaceutical Sciences, 2014)
https://doi.org/10.22034/IJPS.2014.15252 The purpose of the research was to formulate microspheres of acyclovir (ACV) using mucoadhesive polymers, sodium alginate and chitosan. Calcium chloride was used as the ionotropic gelling agent. Sodium alginate was crosslinked by calcium chloride leading to a slower release of the drug. Chitosan which is a cationic polymer interacted with sodium alginate, an anionic polymer, to form an interpolymer complex, which also slowed the release and improved the mucoadhesion. Prior to the formulation, drug: excipient compatibility study was carried out for 12 weeks at 40 ºC ± 2 ºC /75% RH ± 5 RH. Then, FTIR was recorded to check for any chemical degradation of the drug ACV. The morphological properties, the drug encapsulation efficiency, the drug release profile and the ex vivo mucoadhesion strength were investigated. Based on these studies, P8 was found to be the best formulation. P8 had a % cumulative drug release (CDR) of 100.81% at the end of 12 h. High encapsulation efficiency of 80.92% and smaller average particle size of 596.74 μm further favored its selection as the best formulation. P8 followed Higuchi model. Further, SEM of P8 was recorded. Accelerated stability study of P8 for 6 months at 40 ºC ± 2 ºC /75% ± 5% RH indicated that it was stable.